Implementasi Teknologi Laravel dalam Sistem Pemesanan Catering: Inovasi Digital pada Al-Faruq Catering Kudus - Putri, Nabila Shania; Listyorini, Tri; Supriyati, Endang (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2025)
Al-Faruq Catering, like many other catering businesses, faces challenges in managing orders and catering management which are done manually. Inefficient processes often lead to problems such as miscommunication of orders, delays, and suboptimal resource utilization. To overcome these problems, this study aims to implement Laravel technology in the development of a website-based catering ordering system for Al-Faruq Catering Kudus. This system is designed to improve efficiency, accessibility, and operational management through online ordering features, menu management, and digital payment integration. The software development method used is the Waterfall method, which ensures that each stage of development is carried out in a structured and systematic manner, from needs analysis to maintenance. The results of the study show that the use of Laravel as a development framework provides high flexibility, security, and scalability. The implementation of this system has succeeded in significantly improving customer experience and business efficiency. This study contributes to supporting digital transformation in the MSME sector, especially in the catering service sector. By using a Laravel-based approach, Al-Faruq Catering Kudus can meet customer needs more effectively.